(untitled) (Journal of Parents and Teachers, 2014)
Since the birth of Christianity, the birth of Jesus has inspired innumerable works of art. This article presents several pictures on this subject, such as the Adoration of the Shepherds, the Adoration of the Magi or the Mystical Nativity.